Mitochondria and melanosomes establish physical contacts modulated by Mfn2 and involved in organelle biogenesis - Daniele, Tiziana; Hurbain, Ilse; Vago, Riccardo; Casari, Giorgio; Raposo, Graça; Tacchetti, Carlo; Schiaffino, Maria Vittoria (Current biology, 2014)
To efficiently supply ATP to sites of high-energy demand and finely regulate calcium signaling, mitochondria adapt their metabolism, shape, and distribution within the cells, including relative positioning with respect to other organelles. However, physical contacts between mitochondria and the secretory/endocytic pathway have been demonstrated so far only with the ER, through structural and functional interorganellar connections. Here we show by electron tomography that mitochondria physically contact melanosomes, specialized lysosome-related organelles of pigment cells, through fibrillar bridges resembling the protein tethers linking mitochondria and the ER. Mitofusin (Mfn) 2, which bridges ER to mitochondria, specifically localizes also to melanosome-mitochondrion contacts, and its knockdown significantly reduces the interorganellar connections. Contacts are associated to the melanogenesis process, as indicated by the fact that they are reduced in a model of aberrant melanogenesis whereas they are enhanced both where melanosome biogenesis takes place in the perinuclear area and when it is actively stimulated by OA1, a G protein-coupled receptor implicated in ocular albinism and organellogenesis. Consistently, Mfn2 knockdown prevents melanogenesis activation by OA1, and the pharmacological inhibition of mitochondrial ATP synthesis severely reduces contact formation and impairs melanosome biogenesis, by affecting in particular the developing organelles showing the highest frequency of contacts. Altogether, our findings reveal the presence of an unprecedented physical and functional connection between mitochondria and the secretory/endocytic pathway that goes beyond the ER-mitochondria linkage and is spatially and timely associated to secretory organelle biogenesis.